Potensi Asap Cair sebagai Insektisida Nabati Penggerek Buah Kopi Hypothenemus hampei - Gusti Indriati; Samsudin Samsudin (Pusat Penelitian dan Pengembangan Perkebunan, 2018)
Coffee berry borer (CBB) is the main pest of coffee plants. This pest is difficult to control as it attacks coffee fruit on the tree, multiplies inside the fruit and stays till storage. The study aimed to determine the potential liquid smoke from plant waste to control CBB. The research was conducted at Plant Protection Laboratory (IIBCRI), from January to December 2016. The liquid smokes made from cacao pod husks, sawdust, coconut shells, and rice husks. Phytochemical content of liquid smokes was analyzed qualitatively and quantitatively using gas cromatografy mass spectrometry (GCMS). Toxicity analysis was carried out by residual and contact methods at concentrations of 1%; 1.5%; 2%; 2.5%; controls (aquades), and chlorpyrifos insecticide (2 ml/l) as comparison. Each treatment used 15 H. hampei imagos, repeated 3 times. Mortality parameters were observed at 24, 48, 72, 96, and 120 hours after treatment (HAT). To investigate antifeedance, 10 coffee fruits were infested with 20 imagos in plastic containers, repeated 3 times and parameters observed were the number of holes at 1, 2, 3, 4, 5, 6, and 7 days after infestation. The results showed that the largest component in liquid smoke presumably functioned as insecticides are Benzenesulfonic acid 4-hydroxy and Acetic acid. All liquid smokes tested were toxic to CBB imagos. The highest CBB mortalities occurred after liquid smoke treatment from coconut shell at concentrations of 2.5% by 48.87%, attack rate was only 20%, decreased 70%. Liquid smoke from coconut shell is the most potential as botanical insecticide to control CBB.